DNA- and RNA-SIP Reveal Nitrospira spp. as Key Drivers of Nitrification in Groundwater-Fed Biofilters - Arda Gülay (American Society for Microbiology, 2019)
ABSTRACT Nitrification, the oxidative process converting ammonia to nitrite and nitrate, is driven by microbes and plays a central role in the global nitrogen cycle. Our earlier investigations based on 16S rRNA and amoA amplicon analysis, amoA quantitative PCR and metagenomics of groundwater-fed biofilters indicated a consistently high abundance of comammox Nitrospira. Here, we hypothesized that these nonclassical nitrifiers drive ammonia-N oxidation. Hence, we used DNA and RNA stable isotope probing (SIP) coupled with 16S rRNA amplicon sequencing to identify the active members in the biofilter community when subjected to a continuous supply of NH4+ or NO2− in the presence of 13C-HCO3− (labeled) or 12C-HCO3− (unlabeled). Allylthiourea (ATU) and sodium chlorate were added to inhibit autotrophic ammonia- and nitrite-oxidizing bacteria, respectively. Our results confirmed that lineage II Nitrospira dominated ammonia oxidation in the biofilter community. A total of 78 (8 by RNA-SIP and 70 by DNA-SIP) and 96 (25 by RNA-SIP and 71 by DNA-SIP) Nitrospira phylotypes (at 99% 16S rRNA sequence similarity) were identified as complete ammonia- and nitrite-oxidizing, respectively. We also detected significant HCO3− uptake by Acidobacteria subgroup10, Pedomicrobium, Rhizobacter, and Acidovorax under conditions that favored ammonia oxidation. Canonical Nitrospira alone drove nitrite oxidation in the biofilter community, and activity of archaeal ammonia-oxidizing taxa was not detected in the SIP fractions. This study provides the first in situ evidence of ammonia oxidation by comammox Nitrospira in an ecologically relevant complex microbiome. IMPORTANCE With this study we provide the first in situ evidence of ecologically relevant ammonia oxidation by comammox Nitrospira in a complex microbiome and document an unexpectedly high H13CO3− uptake and growth of proteobacterial and acidobacterial taxa under ammonia selectivity. This finding raises the question of whether comammox Nitrospira is an equally important ammonia oxidizer in other environments.